Aplikasi Penampil Informasi Data Tanaman Mangrove Menggunakan QR-Code di Hutan Mangrove Cilacap - Andriansyah Zakaria; Andesita Prihantara; Antonius Agung Hartono; Rostika Lystianingrum; Fadhillah Hazrina (Politeknik Negeri Cilacap, 2020)
EduWisata is a concept of developing an environmentally friendly tourism area by taking into accounts the resources and elements of education in a marine tourism package. The concept has been applied to the Cilacap mangrove forest area. The lack of information media in the mangrove forest area makes the visiting community still not get complete information about the types, classifications, benefits, and distribution of mangrove plants. Quick Response Code or also known as QR Code can be used as a media for storing information based on information technology in the form of a code image. The image of this code can be scanned using a QR code scanner. The QR Code system can also assist managers in improving the quality of service in the delivery of educational information on the types of mangrove plants found in mangrove forests to the public. The QR Code system is made using smartphone technology to scan QR codes. Mangrove plant data information will appear on the visitor's smartphone screen, so visitors will easily access information about mangrove plants.